2008
DOI: 10.1258/jms.2008.008013
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy and socioeconomic deprivation in Gloucestershire

Abstract: Objectives To investigate socioeconomic variations in diabetes prevalence, uptake of screening for diabetic retinopathy, and prevalence of diabetic retinopathy. Methods The County of Gloucestershire formed the setting of the study. A cross-sectional study of people with diabetes was done on a countywide retinopathy-screening database. Diabetes prevalence with odds ratios, uptake of screening, prevalence of any retinopathy and prevalence of sight-threatening retinopathy at screening were compared for different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 14 publications
4
59
3
1
Order By: Relevance
“…parts of London) experience a 25% change in registrations every year. There are few patients in Gloucestershire from ethnic groups, 12 which previous studies 13 have shown can present complex issues with registration. Further, high awareness of the screening programme in Gloucestershire may lead patients with diabetes who have not been offered screening to prompt their GP to include them on the screening programme list.…”
Section: Discussionmentioning
confidence: 99%
“…parts of London) experience a 25% change in registrations every year. There are few patients in Gloucestershire from ethnic groups, 12 which previous studies 13 have shown can present complex issues with registration. Further, high awareness of the screening programme in Gloucestershire may lead patients with diabetes who have not been offered screening to prompt their GP to include them on the screening programme list.…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo, resulta importante la realización de estudios en Chile que validen los distintos modelos de tamizajes y la participación de TM en el proceso. Es conveniente aumentar potencialmente las coberturas, especialmente en los estratos socioeconómicos más bajos que muestran una mayor prevalencia de detección de RD y menores tasas de cobertura en los programas de tamizaje 31,32 . Agradecimientos: Se agradece la cooperación de la Dra.…”
Section: Discussionunclassified
“…Gray 33 has shown a link between the number of reminders required for attendance in the screening programme in Somerset, United Kingdom and the grade of retinopathy identified. In a study 34 in Gloucestershire, United Kingdom, sight-threatening diabetic retinopathy was found to be present most frequently in the most deprived socio-economic group, and this group was the least likely to attend screening.…”
Section: Methodsmentioning
confidence: 98%